Immunoregulatory Effect of Preventive Supplementation of Omega-3 Fatty Acid in a Complex Regional Pain Syndrome Type I Model in Mice - Fernandes, Paula Franson; Galassi, Taynah de Oliveira; Horewicz, Verônica Vargas; Salgado, Afonso Shiguemi Inoue; Mack, Josiel Mileno; Baldança, Heloiza dos Santos; Ferreira da Silva, Ana Paula; Bruehl, Stephen; Bittencourt, Edsel B.; Seim, Lynsey A.; Martins, Daniel Fernandes; Bobinski, Franciane (Frontiers in Integrative Neuroscience, 2022)
Objective: Complex Regional Pain Syndrome (CRPS) is usually triggered by trauma or a surgical procedure, and typically becomes established after an intense inflammatory process with chronic pain and edema as the main symptoms. Available treatments for CRPS have low efficacy. This work aimed to evaluate the clinical and immunoregulatory effects of omega-3 polyunsaturated fatty acid (PUFA) supplementation on paw edema and anti- and pro-inflammatory cytokines and macrophage phenotypes in the Chronic Post-Ischemia Pain (CPIP) preclinical model of CRPS-Type I. Methods: Female Swiss mice were supplemented with omega-3, corn oil, or saline and then submitted to the CPIP model of ischemia/reperfusion (I/R) injury. Supplementation was carried out for 30 days prior to and up to 2 or 15 days after the induction of CPIP, according to experimental protocols. The supplementation protocol included 1,500 mg/kg of omega-3 or corn oil by intragastric route (gavage). Paw edema, interleukin (IL)-4, IL-10, transforming growth factor-β1 (TGF-β1), monocyte chemotactic protein-1 (MCP-1) and tumor necrosis factor (TNF) were then measured in the paw skin and muscle by Enzyme-Linked Immunosorbent Assay (ELISA), and macrophage phenotypes (M1 and M2) assessed in the paw muscle by Western blotting. Results: The CPIP model induced an increase in paw thickness up to 72 h after I/R. Mice supplemented with omega-3 compared to the saline group displayed reduced edema but did not exhibit altered skin IL-4 or skin and muscle TGF-β1, TNF and MCP-1 concentrations, nor did they exhibit significantly altered muscle macrophage phenotype on the second day after CPIP. However, omega-3 supplementation reversed the I/R-related reduction in IL-4 in the paw muscle compared to groups supplemented with saline and corn oil. Furthermore, omega-3 promoted reduction of IL-10 levels in the skin of the paw, compared to animals with lesions supplemented with saline, until the second day after CPIP. On the 15th day after CPIP, IL-10 significantly increased in the muscle of animals supplemented with omega-3 compared to the saline group. Conclusion: Results suggest that omega-3 PUFA supplementation has anti-inflammatory effects in the CPIP model of CRPS-Type I, significantly reducing paw edema and regulating concentrations of anti-inflammatory cytokines including IL-4 and IL-10.